The Alphonsine legislation regarding the prohibition of interfaith sexual contacts : A hermetic or permeable barrier ? - Coulibaly, Pédiomatéhi Ali (Revista Chilena de Historia del Derecho, 2024)
This study deals with the problem of sexual contact between Christians, Jews and Muslims in the Middle Ages through the Siete Partidas of Alfonso X the Wise. Was the barrier erected by this code of laws between these communities watertight or permeable ? This article aims to highlight the way in which Castilian legislation looks at these sexual contacts. The contextualisation of this Code of Laws through the intersection of a variety of sources allows us to understand that the prohibition of this type of sexual relations by the legislation of the Western monarchies in the 13th century was intrinsically impacted by the theses of the Church on this subject. Although the Partidas formally forbid such intimate contact, in practice this ban was not always respected. Thus, many municipal charters (fueros) even sought to regularise the status of the children of such relationships.